EU socio-economic governance in Central and Eastern Europe : the European Semester and national employment policies - Munta, Mario (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book investigates to what extent and how the European Semester impacts on national employment policy in four EU member states of the Central and Eastern European (CEE) region. Using an original theoretical and methodological framework, and based on empirical evidence from extensive interviews with experts in the field, this book examines the relation between EU preferences, exemplified by the yearly list of country-specific recommendations, and national policy responses to EU suggestions, tracing the extent to which policy change can be attributed to the influence of the European Semester. It extracts three potential mechanisms of European Semester influence on policy change: external pressure, mutual learning and creative appropriation and identifies key contributing and inhibiting factors. The book provides several policy recommendations regarding the organisation and workings of the European Semester process. This text will be of key interest to students, academics and practitioners in European and EU politics, EU socio-economic governance, EU social policy, European integration, soft Europeanization and the Europeanization of Central and Eastern Europe"--
Employment policy in the European Semester : an introduction -- Theorizing the influence of the European Semester : mechanisms, conditions and policy change -- Croatia : cherry-picking from the European Semester -- Hungary : a case of neglect? -- Slovakia : reinforcing existing trajectories -- Slovenia : crisis pressure, socialization and strategic use of the European Semester -- How does the European Semester influence employment policies in Central and Eastern Europe? -- Conclusion.
OCLC-licensed vendor bibliographic record.
Keywords: Manpower policy -- Europe, Eastern; Manpower policy -- Europe, Central; Manpower policy -- European Union countries; POLITICAL SCIENCE / General